(untitled) (Jurnal Manajemen dan Kewirausahaan, 2004)
Fundamental changes in the business environment have created a sudden shift of importance of human resource management and human resource functions. The human resource department is being presented with an opportunity to become a significant player on the management team. This is occurring because the human resource function is being transformed into a significant management function. According to researchers and theorists arguments, human assets can be a source of sustained competitive advantage because human assets have tacit knowledge and social complexity that are hard for competitors to imitate. Management practices that are predicted to be sources of sustainable competitive advantage are employment security, selectivity in recruiting, high wages, incentive pay, employee ownership, information sharing, participation and empowerment, self-management teams, training and skill development, cross utilization and cross training, symbolic egalitarianism, wage compression, and promotion from within. Abstract in Bahasa Indonesia : Perubahan-perubahan yang mendasar dalam lingkungan bisnis telah menyebabkan pergeseran dalam urutan pentingnya manajemen sumber daya manusia dan fungsi sumber daya manusia. Departemen sumber daya manusia diberi kesempatan mengambil peran penting dalam tim manajemen. Hal ini terjadi karena fungsi sumber daya manusia sedang berubah menjadi fungsi manajemen yang penting. Menurut pendapat para peneliti dan teoretisi, aset sumber daya manusia dapat menjadi sumber keunggulan kompetitif yang berkelajutan karena aset-aset manusia tersebut mempunyai pengetahuan dan kompleksitas sosial yang sulit ditiru oleh para pesaing. Praktik-praktik manajemen sumber daya manusia yang diperkirakan dapat menjadi sumber keunggulan kompetitif yang berkelajutan adalah kepastian kerja, selektivitas dalam rekrutmen, upah tinggi, upah insentif, kepemilikan karyawan, pembagian informasi, keterlibatan dan pemberdayaan, tim-tim yang diatur sendiri, pelatihan dan pengembangan ketrampilan, penggunaan dan pelatihan silang, kesamaan semua orang, upah/gaji tidak jauh selisihnya, serta kenaikan pangkat bagi orang dalam. Kata kunci: manajemen sumber daya manusia, fungsi sumber daya manusia, keunggulan kompetitif.